A collaborative vision for generating available learning experiences. (26th January 2010) - Mangione, Giuseppina Rita; Anna, Pierri; Salerno, Saverio
The first part of this work collects possible directions of current trends that rule and orientate the dynamics of knowledge (formal, informal), constituting an explanatory premise to the more and more coherent connection between technologies and knowledge seen in its evolution and complexity. In particular, we present the ontology model which the didactic solution of Polo L&K is based on and its applications related to the collaborative vision of learning design, both at a level of macro design (collaborative ontology management) and of micro designing (collaborative based learning experience design).